METHOD COMPARISON OF STATISTICAL AVERAGING ON THE HELMHOLTZ COILS CALIBRATION EXAMPLE - Janeczko, Mariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
During a calibration of Helmholtz coils, in which more than one parameter is measured directly, there are various approaches to statistical averaging. In this paper will be discussed two of them: the averaging at the beginning of directly measured magnitude and the averaging of the final value. In order to compare the methods they will be referenced to the Monte Carlo method, having regard to the uncertainty of type A.